Endoscopic Resection of Lower Ureter in Upper Urinary Tract Tumors - Mohammadzadeh Rezaee, Mohammad Ali (Urology Journal, 2009)
Purpose: To evaluate the efficacy and safety of endoscopic resection of lower ureter in upper urinary tract tumor cases. Materials and Methods: Five patients with transitional cell carcinoma (TCC) of the upper urinary tract were enrolled in this study. Nephrectomy was carried out through a flank incision and distal ureter with a cuff of bladder, which was removed using endoscopic approach. Complications and recurrence rate were evaluated. Results: A total of 5 patients with upper urinary tract tumor underwent the endoscopic resection of lower ureter. All the patients had grade I transitional cell tumor. Two patients had suffered from bladder TCC treated previously. During the follow-up two cases developed bladder tumor: one, 18 months and another, one year postoperatively, both in the base of bladder, which was managed successfully by transurethral resection (TUR). Conclusion: Endoscopic resection of lower ureter in selected patients with upper urinary tract tumors can lead to lower morbidity, shorter operation time, and higher patient's satisfaction. Despite the minority of cases in this study, it seems that this method is applicable in selected cases.